Chronotopische Strukturen der doppelten Welt von E. T. A. Hoffmann - Audzei, Zinaida (Literatūra, 2016)
Hoffmann’s unique position in the Romantic period is based on various aspects in his poetry. Non other than Freud wrote about Hoffmann’s ability to create insecurity on the percipient’s part, especially intensified by depicting doppelgänger – mysterious and real at the same time, as the whole world turns out to be. The article took up Bachtin’s idea of the so called chronotopos and scrutinizes Hoffmann’s texts with regard to this system of time and space. In Hoffmann’s narrative literature there is already the distinction between two worlds – the phantastic one of the protagonist on the one hand, the common world of the apparently levelheaded bourgeois on the other hand. They are not strictly separated as in former poetry of the romantic period, just symbolically marked on the crossover spots. Hoffmann’s outstanding skill lies in the connection of diverging elements, not only of the already mentioned two worlds but as well of time and space which might be felt and noticed in a different way both by the various characters and one single person as well. Also a cyclic development is often embedded in the poetic action reminding of mythical constellations and interpreted as a reconstruction of a mythical genealogy.The article aims to analyse tales and novellas regarding the unique sensation of time and space using Hoffmann’s “The Golden Pot”, “Princess Brambilla”, “A Report on the Latest Adventures of the Dog Berganza” or “A New Year’s Eve Adventure”. The author’s world seems a balance act and is marked with certain symbols and components, which prove that the real and the mythical world are not strictly separated.
Keywords: Chronotopos; Märchen; Mythos; fantastisch; zyklische Entwicklung; das Goldene Zeitalter; Ritus; romantische Doppelwelten